PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN SELF EFFICACY TERHADAP BUDAYA KERJA DAN WORK ENGAGEMENT DI DINAS PERHUBUNGAN PROVINSI DKI JAKARTA (PADA ASN GENERASI MILENIAL) - Fransisca, (2021)
Work engagement is an attitude that depicts an individual fully engaging with his or her work both emotionally and physically by exhibiting passionate, dedicated, and imaginary behaviour in doing the work. Many factors that can play a role in improving work engagement such as Perceived organizational support (POS), Self Efficacy and Work behaviour. The purpose of this quantitative research that aim to determine the influence of POS and Self Efficacy of work behaviour and work engagement. The millenial Civil employees of Jakarta Transportation Department became the population in this study. The number of samples used in this study was 87 respondents, using the simple random sampling method. Data is collected by distributing questionnaires. The analysis technique used is Structure Equation Models (SEM) with Partial Least Square (PLS). The result of this study indicate (1) POS has not effect on work engagement with a path coefficient of 0,083. (2) Self efficacy has not effect on work engagement with a path coefficient of 0,161. (3) POS has effect on work behaviour with a path coefficient of 0,178. (4) Self efficacy has an effect on work behaviour with a path coefficient of 0,717. (5) Work behaviour has an effect on work engagement with a path coefficient of 0,705.